Waste to energy conversion: Pyrolytic oil and biodiesel as a renewable fuel blends on diesel engine combustion, performance, and emissions. Issue 12 (26th September 2022) - Sönmez, Halil İbrahim and Okumuş, Fatih and Kaya, Cenk and Aydin, Zafer and Safa, Aykut and Kökkülünk, Görkem
ABSTRACT: The use of pyrolytic oil (WTPO) obtained from waste vehicle tires in Turkey is evaluated and encouraged within the scope of YEKDEM (Turkey Renewable Energy Resources Support Mechanism). In order to benefit from this incentive, WTPO must be used as the main fuel in diesel engines. For this reason, in this study, unlike all other studies in the literature, the use of WTPO at a high rate was examined. The effects of biodiesel and WTPO mixtures containing high WTPO on engine performance and emissions were investigated. The experiments were carried out at 2800 rpm engine speed, where the maximum power was obtained, and at 4 different loads as 100%, 75%, 50%, and 25%. When the obtained results are examined. The lowest brake thermal efficiency (BTE) value was obtained in P100 fuel at 25% load and its value was 16.21%. Brake specific fuel consumption (BSFC) data were similar for all test fuels under the same load conditions. Based on the heat release rate and in-cylinder pressure data, it was noted that biodiesel reduced the ignition delay time. The maximum in-cylinder temperature was 1723.4 K and the maximum exhaust temperature was 590°C with the use of P60B40 fuel. The lowest nitrogen oxides (NOx) value results were obtained at 100% load. Hydrocarbon (HC) emissions decreased from 1.13 g/kWh to 0.13 g/kWh for P100 fuel as load increased form 25% to 100%. All these results show that although the biodiesel additive slightly worsened the emissions, positive results were obtained for the performance data.